2015
DOI: 10.1590/s1413-70542015000500010
|View full text |Cite
|
Sign up to set email alerts
|

Tapioca and Rice Flour Cookies: Technological, Nutritional and Sensory Properties

Abstract: Tapioca flour is derived from the starch extracted from manioc and is a widely used food product in Brazil. Rice flour is produced from grains of rice and is used in the production of bread, porridge, cakes and cookies, which are recommended for people with celiac disease. The goal of this work was to add value to the aforementioned products by developing cookies based on tapioca and rice flours. Five formulations were prepared: A 100:0, B 75:25, C 50:50, D 25:75 and E 0:100 to tapioca and rice flour respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 10 publications
1
6
0
10
Order By: Relevance
“…This pattern especially was found in TN 66, this may be explained by higher crude fiber of TN 66. This result was also observed by Montes et al [19], who observed that cookies containing tapioca and rice flour displayed higher hardness.…”
Section: Texture Profile Analysis (Tpa) Of Steamed Rice Bowl Cakesupporting
confidence: 86%
“…This pattern especially was found in TN 66, this may be explained by higher crude fiber of TN 66. This result was also observed by Montes et al [19], who observed that cookies containing tapioca and rice flour displayed higher hardness.…”
Section: Texture Profile Analysis (Tpa) Of Steamed Rice Bowl Cakesupporting
confidence: 86%
“…On the other hand, for consumers in the age group (b), there was a decrease in the evaluations, but, for the 5% and 15% formulations, the testers stated that they liked it slightly (score 6.0), presenting a higher acceptability index than the sample containing only wheat flour. These results demonstrate that cookies made from the CAB flour presented similar acceptability to the cookies of commercial wheat flour, grape marc, banana, rice, and tapioca [50,56,57] before the evaluators, highlighting the age group A and making it promising in the supplementation and incorporation in food formulations improving the nutritional properties. Cookies made with different proportions of CAB flour are shown in Figure 3.…”
Section: Sensory Analysis Of Cookiesmentioning
confidence: 71%
“…Berdasarkan Standar Nasional Indonesia (01-2973-1992 kadar protein biskuit adalah minimal 6% dan hasil analisis kadar protein cookies tersebut antara 2.74-3.40% (Tabel 3). Cookies berbagai variasi perbandingan tepung beras, tepung tapioka, dan tepung maizena memiliki rentang kadar protein yang sama dengan cookies yang dibuat dari campuran tepung beras dan tepung tapioka 25%:75% serta 50%:50% (Montes et al, 2015). Cookies dengan perbandingan tepung beras, tepung tapioka, tepung maizena sebesar 45:45:10 memiliki kadar protein paling rendah dan perbandingan 65:35:5 memiliki kadar protein paling tinggi.…”
Section: Kadar Proteinunclassified
“…Hal ini menunjukkan cookies tersebut memiliki kandungan serat kasar yang tidak sesuai dengan SNI. Namun, kadar serat kasar tersebut sesuai dengan standar cookies Brasil yaitu minimal 3% (Montes et al, 2015). Cookies berbahan baku campuran tepung beras, tepung tapioka, dan tepung maizena bisa menjadi kue kering yang lebih menyehatkan karena kandungan serat kasar yang lebih tinggi.…”
Section: Kadar Serat Kasarunclassified